Role of Tropical Cyclones in Determining ENSO Characteristics - Li, Hui; Hu, Aixue; Meehl, Gerald A. (Geophysical research letters, 2023)
El Niño‐Southern Oscillation (ENSO) can effectively modulate global tropical cyclone (TC) activity, but the role TCs may play in determining ENSO characteristics remains unclear. Here we investigate the impact of TC winds on ENSO using a suite of Earth system model experiments where we insert TC winds, extracted from a TC‐permitting high‐resolution simulation, into a low‐resolution model configuration with nearly no intrinsic TCs. The presence of TC winds in the model increases ENSO power and shifts ENSO frequency closer to what we observe. TCs lead to an increase of strong to extreme El Niño events seen in observations and not simulated in the low‐resolution model without intrinsic TCs, mainly through enhanced zonal advection feedback and thermocline feedback. Our results indicate that TCs play a fundamental role in producing the ENSO characteristics we experience today in the climate system and point to a two‐way climatological interaction between TCs and ENSO. Plain Language Summary El Niño‐Southern Oscillation (ENSO) can influence global tropical cyclone (TC) activity by altering the large‐scale conditions. TCs, as transient yet powerful weather events, can cause strong air‐sea interactions over the tropical ocean that may consequently influence the climate mean state. Here we show how TCs could be essential to the characteristics of ENSO using a suite of Earth system model experiments where we insert TC winds, extracted from a high‐resolution model simulation, into a low‐resolution model simulation with nearly no intrinsic TCs. The added TC winds in the model increases ENSO power and shifts ENSO frequency closer to the observations. TCs lead to an increase of strong to extreme El Niño events seen in observations and not simulated in the low‐resolution model without intrinsic TCs. Our results indicate that TCs play a fundamental role in producing the ENSO characteristics we experience today in the climate system and point to a previously unidentified two‐way climatological interaction between TCs and ENSO. Key Points The climatological impacts of tropical cyclone (TC) winds on El Niño‐Southern Oscillation (ENSO) are investigated for the first time in a fully coupled Earth system model TC winds impact ENSO magnitude, frequency, and the occurrence of strong to extreme El Niño events Model proved that TC winds affect El Niño by enhancing the thermocline feedback and the zonal advection feedback